MORNING RESPONSES OF CALLIPHORID AND SARCOPHAGID PREPUPAE TOWARDS DIFFERENT PUPATION MATERIALS - A. Ghafoor; M. Akbar; M. Ansar; I. Amjad; M. S. Khan; M. Ashraf (Journal of Animal and Plant Sciences, 2010)
An experiment was conducted to evaluate the pupation site preference of Calliphorid and Sarcophagid flies towards the various pupation materials in the months of October and December. Flies were released in the two batches of “10” and “50”.  Six pupations materials were the news paper strips, fresh leaves, dry leaves, decayed fruits, decayed vegetables and folded clothes. Data were recorded for fifteen minutes for five consecutive days.  Results showed that decayed vegetables proved the best sites for pupation in both batches “10’ and “50” respectively during the month of October. In the month of December decayed fruits and fresh leaves proved the most preferred site in the batches of “50”. and “10” respectively. In both months and batches folded clothes found the least attractive site for pupation.
Keywords: morning response; Calliphorid; Sarcophagid; pupation materials